ARCHETYPICAL MODEL OF SEMANTIC COMPATIBILITYOF MEDICAL INFORMATION SYSTEMS PROJECTING - HAHEN, Valentyn (Herald of Khmelnytskyi National University. Technical sciences, 2022)
There are a few different ways to think about semantic compatibility in the context of electronic health records (EHRs). One way to think about it is in terms of the structure of the data. This would involve making sure that the data is organized in a way that is consistent with how other systems expect it to be organized. Another way to think about it is in terms of the meaning of the data. This would involve making sure that the data is annotated in a way that is consistent with how other systems expect it to be annotated. A third way to think about semantic compatibility is in terms of the use of the data. This would involve making sure that the data is used in a way that is consistent with how other systems expect it to be used. Each of these approaches has its own strengths and weaknesses. The approach that is most appropriate will depend on the specific context in which the EHR is being used. The structure of the data is the most important factor to consider when thinking about semantic compatibility. This is because the structure of the data determines how the data is organized and how it is accessed. If the structure of the data is not compatible with the structure of other systems, then the data will not be accessible to those systems. The meaning of the data is also important to consider when thinking about semantic compatibility. This is because the meaning of the data determines how the data is interpreted. If the meaning of the data is not compatible with the meaning of other systems, then the data will not be interpreted correctly by those systems. The use of the data is also important to consider when thinking about semantic compatibility. This is because the use of the data determines how the data is used. If the use of the data is not compatible with the use of other systems, then the data will not be used correctly by those systems. In general, the most important factor to consider when thinking about semantic compatibility is the structure of the data. The meaning of the data and the use of the data are also important factors to consider, but they are not as important as the structure of the data.
Keywords: medical information system; data exchange; semantic compatibility